Parametric Evaluation of a Single Cylinder Diesel Engine Fueled with Goat-Urine Emulsified Diesel - Katare, Pravin; Kumbhar, V. S.; Tirpude, R. B.; Dalkilic, Ahmet Selim; Chan, Choon Kit (SPRINGER HEIDELBERG, 2025)
Considering stricter emission norms, different emission reduction strategies have been studied by researchers. In this work, experimentation has been performed to analyze the influence of goat urine emulsified diesel on the combustion, emission, and performance characteristics of the single cylinder engine fuel and their comparison with conventional diesel operation. Goat urine is abundantly available across India, and its mixture with water improves its thermal performance and reduces NOx emissions. Non-ionic surfactants like Tween 80 and Span 80 have been used in the emulsification process. Based on volume, 5%, 10%, and 15% goat urine were used for emulsion purposes. The compression ratio and injection pressure were maintained at about 18:1 and 600 bar, respectively. The tests were conducted for 3, 6, 9, and 12 kg loads. From the results, for the 12 kg loading condition, in comparison with diesel combustion, there was a 52%, 30%, 65%, and 73% reduction in NOx, CO, HC, and smoke opacity, correspondingly, for GU15:D85 (15% goat urine and 85% diesel). An increase in thermal efficiency has been achieved up to 9 kg, maximum rise is about 12% for the G10:D90 fuel combination but for 12 kg, it gets reduced for all the emulsion samples. As far as emissions and thermal efficiency are considered, G10:D90 (10% goat urine and 90% diesel) is the best possible combination for selected working conditions.
Keywords: Environmental pollution; Clean fuel; Goat urine; Emulsification; Non-ionic surfactants; EMISSION CHARACTERISTICS; WATER; PERFORMANCE; COMBUSTION; BIODIESEL; Science & Technology - Other Topics